Digital transformation and internationalization strategies in organizations - Yildiz, Orkun, 1987- (Advances in business strategy and competitive advantage., 2022)
"This book covers a wide range of issues and topics related to digital transformation and internationalization strategies on institutional governance such as employment, quality management, system design and control, education and language policies, business and law models for the organizations"--